Emergent EEG in Status Epilepticus: Off-Hours Delays Limit Clinical Utility - Teemu Pöytäkangas; Pabitra Basnyat; Jukka Saarinen; Sirpa Rainesalo; Jukka Peltola (Clinical EEG and Neuroscience, 2026)
Background To evaluate the use, diagnostic yield, and timing of EEG in emergency department (ED) patients receiving second-line intravenous antiseizure medication (IV ASM). Methods We retrospectively reviewed patients aged ≥16 years who received IV ASM at Tampere University Hospital over one year. Episodes were categorized by status epilepticus (SE) subtype and arrival time (office vs off-hours). Timing of ASM/EEG and EEG's diagnostic contribution were analyzed. Results We identified 132 episodes in 116 patients (41% female; median age 66 years). Convulsive SE (CSE) was most common (n = 41), followed by nonconvulsive SE (NCSE, n = 21), comatose SE (n = 10), and focal aware SE (FASE, n = 8). Recurrent seizures (n = 32) and postictal states (n = 20) were also included to highlight diagnostic challenges. Median IV ASM timing was 55 min post-ED arrival. EEG was substantially delayed (median 13 h 34 min). 70% arrived off-hours, when EEGs were performed less frequently (63% vs 87%; p = 0.006) and later (16 h 12 min vs 2 h 41 min; p < 0.001). In 94% of off-hours cases, ASM was given before EEG. EEG was diagnostic in 86% NCSE and 80% comatose SE cases. Post-treatment, EEG revealed ongoing SE in 39% overall (15% CSE). Conclusions EEG is essential for diagnosing NCSE and comatose SE and for assessing treatment response in all SE types. However, marked delays, particularly during off-hours, limit its clinical utility. Improving rapid EEG access in ED may enhance diagnostic accuracy and guide timely therapeutic decisions.